2017
DOI: 10.1080/0284186x.2017.1312014
|View full text |Cite
|
Sign up to set email alerts
|

Associations between volume changes and spatial dose metrics for the urinary bladder during local versus pelvic irradiation for prostate cancer

Abstract: Substantial bladder volume changes during the treatment course occurred even though patients were treated under a full bladder/daily image-guided protocol. Larger bladder volumes resulted in less bladder wall spared at the posterior-inferior sector, regardless the treatment received. Contrary, larger bladder volumes meant larger delivered doses to the superior bladder sector for pelvic RT but smaller doses for local treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…And MR-biomonitoring and adaptive treatment are currently evolving in prostate cancer and other tumor entities [7]. Reduction of the planning target volume (PTV) margins due to improved definition of the prostate including dominant lesions, i.e., the intraprostatic tumor by MRI or PET [8], is impeded by inter-and intrafractional organ movements of prostate and surrounding organs at risk (OAR) like bowel and bladder volume changes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…And MR-biomonitoring and adaptive treatment are currently evolving in prostate cancer and other tumor entities [7]. Reduction of the planning target volume (PTV) margins due to improved definition of the prostate including dominant lesions, i.e., the intraprostatic tumor by MRI or PET [8], is impeded by inter-and intrafractional organ movements of prostate and surrounding organs at risk (OAR) like bowel and bladder volume changes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, changes in bladder filling, shape and position during the RT course have been extensively reported [12,14,16,30], and are major reasons for the differences between planned and delivered DVH metrics [13]. In the previous study, we also demonstrated that the posterior/inferior bladder wall tended to move towards the high dose region when the bladder volume increased [22]. In the present study, we observed larger delivered bladder volumes compared to planned for cases, and smaller delivered compared to planned for controls (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Treatment could be interrupted or adapted if intra-fraction motion exceeded a certain threshold. This could be addressed by electromagnetic transponders, for example using the Calypso system for prostate radiotherapy, or by MRI-delivered treatments such as the MR-Linac [37,56]. However, the additional equipment and need for implantation may limit more general use of electromagnetic transponders and the complexities of rapid daily adaptive replanning at present represents a challenge to the routine use of the MR-Linac.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate radiotherapy, implanted electromagnetic transponders such as the Calypso 4D localisation system (Calypso Medical Technologies, Seattle, USA) can monitor for interfractional changes in prostate position [37]. In addition, these also permit real time tracking, providing the potential to correct for intra-fractional prostate motion and gating of the radiation beam if intra-fraction motion exceeds a certain threshold.…”
Section: Electromagnetic Transpondersmentioning
confidence: 99%
See 1 more Smart Citation